Acidic Residues in the Hfq Chaperone Increase the Selectivity of sRNA Binding and Annealing. Issue 22 (6th November 2015) - Panja, Subrata; Santiago-Frangos, Andrew; Schu, Daniel J.; Gottesman, Susan; Woodson, Sarah A.
Abstract: Hfq facilitates gene regulation by small non-coding RNAs (sRNAs), thereby affecting bacterial attributes such as biofilm formation and virulence. Escherichia coli Hfq recognizes specific U-rich and AAN motifs in sRNAs and target mRNAs, after which an arginine patch on the rim promotes base pairing between their complementary sequences. In the cell, Hfq must discriminate between many similar RNAs. Here, we report that acidic amino acids lining the sRNA binding channel between the inner pore and rim of the Hfq hexamer contribute to the selectivity of Hfq's chaperone activity. RNase footprinting, in vitro binding and stopped-flow fluorescence annealing assays showed that alanine substitution of D9, E18 or E37 strengthened RNA interactions with the rim of Hfq and increased annealing of non-specific or U-tailed RNA oligomers. Although the mutants were less able than wild-type Hfq to anneal sRNAs with wild-type rpoS mRNA, the D9A mutation bypassed recruitment of Hfq to an (AAN)4 motif in rpoS, both in vitro and in vivo . These results suggest that acidic residues normally modulate access of RNAs to the arginine patch. We propose that this selectivity limits indiscriminate target selection by E . coli Hfq and enforces binding modes that favor genuine sRNA and mRNA pairs. Graphical abstract: Highlights: Hfq chaperones bacterial sRNAs during stress and pathogenesis. E . coli Hfq normally selects cellular RNAs containing UUU or AAN sequence motifs. Mutating acidic residues near the Hfq active site makes it less selective. Asp9-to-Ala mutation bypasses recruitment of Hfq to AAN sites in mRNAs. Acidic residues help Hfq discriminate between correct and non-specific targets.